Vitamin A Supplementation Programs and Food Diversity in Stunting Prevention in North Sumatra: Lessons from the Indonesian Nutritional Status Survey 2022 - Masthalina, Herta; Letelay, Alfons Maryono; Doloksaribu, Tetty Herta; Sudaryati, Etti (Universitas Airlangga, 2026)
This study used cross-sectional data from the 2022 Indonesian Nutritional Status Survey to examine vitamin A supplementation, dietary diversification, and stunting in North Sumatra, including a group of 7,973 children aged 6–23 months. The results indicated that 62.7% of the youngsters took vitamin A and 39.4% had diversified diets. Multivariate analysis indicated that children lacking vitamin A supplementation were associated with a 1.43-fold increased proportion of stunting (CI: 1.27-1.61), and children with non-diverse diets had a 1.21 times higher risk (CI: 1.10-1.37). Regional stratification analysis revealed that a lack of vitamin A supplementation in rural areas increased the risk of stunting by a higher factor (OR: 1.49; CI: 1.25-1.78) in cities (OR: 1.38; CI: 1.18-1.61). The impact of dietary diversity on stunting was more substantial in rural areas (OR: 1.28; CI: 1.07-1.53) compared than in urban areas (OR: 1.15; CI: 0.98-1.35). The results recommend improving program coverage and nutrition education to account for local differences.